Supplementation of gluten-free sorghum flour-based dog treats with soluble animal proteins - Lema Almeida, Krystina Alejandra (Kansas State University, 2021)
Pet treats are given to dogs to strengthen pet and owner ties and as a reward. Most treats available on the market are baked and based on wheat. Alternatively, sorghum is a gluten-free grain that provides antioxidants and has slow starch digestibility. Sorghum might be used to produce dog treats as an alternative for pet owners looking for healthy foods. However, because it lacks gluten, functional proteins to help with binding are required. The objective of this study was to determine the effect of adding soluble animal proteins to whole sorghum flours in lieu of whole wheat on the physical, nutritional, and preference of rotary molded baked dog treats. The experiment was conducted in triplicate as a 2x4+1 augmented factorial arrangement of treatments. Two whole sorghum flours (white [WWS] and red [WRS]), four protein sources (none [NC], spray-dried plasma [SDP], egg protein [EP], and gelatin [GL]), and a control with whole wheat flour [WWF-GTN] were evaluated. Higher crude protein and lower total starch (TS), total digestible starch (TDS), resistant starch (RS), peak viscosity (PV), total viscosity (TV), and setback viscosity (SBV) were found in WWF as compared to the WWS or WRS (P<0.05). A similar final dough temperature (24 -26°C) was achieved across treatments. The dough moisture, dough weight, and evaporation rate were influenced by the water-binding ability of the proteins and the water added. The WRS treatments were heavier (P<0.05) than the WWS. Due to differing water addition to achieve a machinable dough, the moisture fluctuated from 27.23% to 36.39%, wherein the NC treatments had the highest moisture, followed by GL, SDP, WWF-GTN, and EP (P<0.05). The NC treatments had the highest evaporation rates (17.35% and 16.31%), and the EP treatments the lowest (9.66% and 11.7%) for WWS and WRS, respectively (P<0.05). The dog biscuits had similar dry matter (>92.0%), Aw (<0.65), and caloric content (3.40-3.54 Kcal/g). However, the EP treatments had the highest crude protein (>17.8%) and the NC treatments the lowest (<10.2%; P<0.05). The ash for the SDP treatments was higher (>2.9%; P<0.05) than all others. The values for rapidly digestible starch (RDS) and RS increased after baking. The SDP, EP, and GL treatments had comparable RDS values but lower than WWF-GTN or NC (P<0.05); nonetheless, no differences across treatments occurred for RS. Also, the TDS and TS declined due to dilution from the added protein sources with no protein or cereal ingredient main effect. The texture of the sorghum treatments was enhanced by the proteins added. The EP were the hardest treatments, followed by those with SDP and GL (P<0.05). The NC treatments were very brittle and were not comparable in dimensions or texture to the other treatments since they had to be sheeted and cut because they would not extract intact from the die roll. The thickness of large and small WWF-GTN biscuits was greater (P<0.05) compared to the sorghum treatments. The color of the biscuits was influenced by the proteins and cereals used, being lighter (P<0.05) for those with WWS, WWF, and GL or NC. The dogs did not exhibit a preference between WWF-GTN, WWS, or WRS treats when evaluated together. However, when evaluating WWS treats, the dogs preferred WWF-GTN, and those which included SDP and EP (P<0.05). The dogs had difficulty eating the EP treatments due to their hard texture. When assessed by a trained sensory panel variation across treatments for appearance and texture was high. The WRS and WWS biscuits with SDP or EP resulted in a darker appearance, while NC biscuits had more surface cracks. Initial crispness, hardness, and fracturability were greater for EP than all other protein-containing treatments. The WWF-GTN was in between the sorghum treatments regarding hardness. The sensory panel identified the predominant flavor and aftertaste as grainy. Volatile assessment for hexanal among all treatments was <1.0 mg/kg except for the EP treatments which ranged from 2.0 to 19.3 mg/kg over the duration of the evaluation (112 days at 30°C - 60% RH). This work indicated that WWS and WRS coupled with soluble animal proteins like GL or SDP could produce suitable baked treats for dogs comparable to wheat. Additional refinement will be necessary to produce treats in a commercial setting.
Keywords: Baking; Dogs; Gluten-free; Rotary molding